Obtenção de carvão ativado impregnado com prata para fins bactericidas - Ribeiro, Gabrielly Vieira (2014)
The development of products with antimicrobial, inhibitory or even lethal action has attracted considerable attention in widely different research and applications fields. The present work studies the obtaining of an antimicrobial material derived from activated carbon submitted to adsorption in a medium with silver ions. It s divided into five chapters, dealing respectively of: introduction (subject s delimitation; research objectives; study s structure); literature review (antimicrobial materials, metal ions, activated carbon impregnated with silver (ACIS); ACIS s details of obtaining and applications); materials and methods (type of research, experiments, characterization tests); results and discussions and conclusions. To characterize the material obtained, in addition to the surface area analysis, inhibitory and bactericidal effects of the samples were evaluated by microbiological testing with different bacteria. About the experimental methodology, it was tested the effects of the silver ions impregnated on coal in cultures of bacteria Escherichia coli and Staphylococcus aureus from different strains. These effects were evaluated by minimum inhibitory concentration and minimum bactericidal concentration tests. The results for the material obtained confirmed the action of silver as an important antibacterial agent.